2013
DOI: 10.1016/j.chom.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Induces the Formation of Stable Microtubules to Enhance Early Infection

Abstract: Summary Stable microtubule (MT) subsets form distinct networks from dynamic MTs and acquire distinguishing posttranslational modifications, notably detyrosination and acetylation. Acting as specialized tracks for vesicle and macromolecular transport, their formation is regulated by the end-binding protein, EB1, which recruits proteins that stabilize MTs. We show that HIV-1 induces the formation of acetylated and detyrosinated stable MTs early in infection. Although the MT depolymerizing agent nocodazole affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
170
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(176 citation statements)
references
References 39 publications
4
170
2
Order By: Relevance
“…For example, it was reported that HIV-1 intracellular trafficking requires the formation of acetylated and detyrosinated stable MT tracts [78]. The end-binding protein EB1 mediates the virus-induced tubulin acetylation, and HIV-1 matrix protein targets the EB1-binding protein Kif4 to induce MT stabilization.…”
Section: Post-entry and Nuclear Targetingmentioning
confidence: 99%
“…For example, it was reported that HIV-1 intracellular trafficking requires the formation of acetylated and detyrosinated stable MT tracts [78]. The end-binding protein EB1 mediates the virus-induced tubulin acetylation, and HIV-1 matrix protein targets the EB1-binding protein Kif4 to induce MT stabilization.…”
Section: Post-entry and Nuclear Targetingmentioning
confidence: 99%
“…HIV-1 infection was also shown to induce tubulin post-translational modifications that are associated with the formation of a more stable subset of MTs, thus facilitating translocation of HIV-1 across the cytoplasm (80,91). Virus-induced MT stabilization, which occurs very rapidly after cell entry (within 1-2 h post-infection), was found to involve EB1 (91) and, albeit to a lesser extent, MAP1A/MAP1S proteins (80).…”
Section: Maps Mediate Virus-induced Microtubule Stabilizationmentioning
confidence: 99%
“…Virus-induced MT stabilization, which occurs very rapidly after cell entry (within 1-2 h post-infection), was found to involve EB1 (91) and, albeit to a lesser extent, MAP1A/MAP1S proteins (80). Conversely, HIV-1 infection was impaired by overexpression of moesin, a member of the ezrin, radixin and moesin (ERM) family that negatively regulates the stable MT network (101), thus confirming that MT stabilization favors viral particle trafficking to their site of replication.…”
Section: Maps Mediate Virus-induced Microtubule Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ϫ .E Ϫ HIV-1-based plasmid lacking env and vpr genes and having an mCherry open reading frame (ORF) instead of the nef gene, together with a VSV-G expression plasmid (13). We used a VSV-G envelope to bypass cell entry limitations and to look specifically at postentry events.…”
Section: Transduction Of Primary Cord-derived Cd34mentioning
confidence: 99%